Strategi Pembelajaran Guru Pada KB. Permata Hijau (Telaah Terhadap Sekolah Tertinggal di Kabupaten Polewali Mandar) - Hasana; Salis Khoiriyati; Dwi Bhakti Indri M (Atthiflah: Journal of Early Childhood Islamic Education, 2020)
This journal discusses the application of learning strategies used by teachers in early childhood in 2020-2021. This research is motivated by the implementation of various strategies that have been and have not been optimally applied in teaching and learning activities so far. The purpose of this research is to find data, information and find out about the implementation of learning strategies in family planning. Green Gem for the year2020-2021. The type of research used is a type of qualitative research through a case study approach carried out at KB Permata Hijau for the 2020-2021 academic year. KB. Permata Hijau was used as a source of data to obtain teacher data and to find out the implementation of the teaching strategies used by the teacher. The data were obtained using the interview method and documentation method. After the data is collected, it is analyzed interactively and lasts until it is complete. Then it is described descriptively, which is manifested in the form of a detailed description. This research shows that the implementation of learning strategies carried out by teachers to early childhood in the academic year 2020-2021 has been implemented properly in accordance with the theory that has been put forward.